Exploring the creativity-curiosity link in early childhood - Julie Vaisarova; Lezxandra Saguid; Anne S. Kupfer; Helena S. Goldbaum; Kelsey Lucca (Journal of Creativity)
Childhood is a pinnacle of both creativity and curiosity, and although these constructs theoretically overlap, few studies have probed whether they are directly related in childhood or driven by similar cognitive and emotional processes. Across two online Zoom sessions, 36 3- to 6 year-olds completed six tasks measuring diverse manifestations of curiosity and creativity, as well as tasks assessing vocabulary, self-esteem, and executive function. Caregivers also completed questionnaires regarding their children's curiosity. Only two significant, positive correlations were found between indices of creativity and curiosity: between originality of ideas (creativity) and breadth of exploration (curiosity), and between creativity on a production-based task and parent-reported breadth of exploration (curiosity). Further, the two constructs were predicted by different child characteristics. Age was the main predictor of creativity; originality of children's ideas in two divergent thinking tasks decreased with age, while fluency and holistic ratings of production-based tasks increased. Self-esteem, in turn, was the strongest predictor of curiosity, correlating positively with several subtypes of parent-reported curiosity. The results of this exploratory study suggest creativity and curiosity may not be as closely linked in childhood as some have proposed, and that pinpointing their relations will require careful attention to the individual components and expressions of each construct.